Impacts of COVID-19 on Owner's Veterinary Healthcare Seeking Behavior for Dogs With Chronic Conditions: An Exploratory Mixed-Methods Study With a Convenience Sample - Owczarczak-Garstecka, Sara C.; Furtado, Tamzin; Graham, Taryn M.; Lloyd, Imogen; Singleton, David A.; Wallis, Lisa; Westgarth, Carri (Frontiers in Veterinary Science, 2022)
This mixed-method study explored the impacts of the COVID-19 pandemic on owners’ veterinary healthcare seeking, with particular focus on dogs with chronic conditions. A convenience sample of 719 UK dog owners completed an online survey (December 2020-January 2021). Differences in treatment provision and respondents’ decisions to seek care across acute, preventative, chronic conditions and for end-of-life care were explored. Multivariable logistic regression models were used to identify factors associated with seeking care for any health issue compared to deciding against it, and urgency to seek care given symptom that could indicate chronic conditions. Open-ended questions were analysed by thematic analysis. Significant (p-value<0.05) differences in care seeking decisions were identified regarding access to veterinary care and the way treatment was provided across all health issues. The top reasons for not seeking care across all health issues were a lack of access to a veterinarian (29.9%, n=56/187) and a reluctance for a dog to go to the clinic unaccompanied (20.3%, n=38/187). Variables related to stronger dog-owner relationship, higher confidence in seeking care, perception of: benefits of veterinary care, dog’s high susceptibility to illness and high severity of dog’s condition, increased the odds of seeking, and urgency to seek, care. A dog’s chronic illness diagnosis reduced the odds of seeking care during the pandemic, reportedly due to difficulties in accessing care for non-urgent issues. Qualitative analysis showed that limited access to routine consultations, delays in test results and restricted access to complementary treatments, led some owners of dogs with chronic conditions to believe that their dog’s welfare had deteriorated during the pandemic. Pandemic control measures necessitated changes to how consultations were run. These changes were often viewed favourably, but dog-client separation during consultations were considered problematic, sometimes delaying veterinary advice-seeking, including for euthanasia. Separating owners from their dogs during veterinary consultations should be avoided wherever possible due to impacts on dogs, owners and healthcare seeking. Interventions to improve veterinary healthcare seeking could target attitudes toward benefits of seeking care, improve owners’ self-efficacy and capitalise on the dog-owner bond. Such interventions should be implemented alongside interventions aimed at removing structural barriers to accessing healthcare.